RAQAMLI TEXNOLOGIYALAR DAVRIDA O‘QITUVCHINING KASBIY RIVOJLANISHI - Gilishtaganova, O.M. (SCIENCE and SOCIETY, 2024)
This article analyzes the professional development of a teacher in the digital age, the requirements for the quality and effectiveness of education, the content and ways to implement the transition of the digital environment to activity, the basic concepts of «professional development of a teacher» and «teacher support in professional development». It also covers several opportunities to support the professional development of teachers and the transfer of learning to a digital educational environment.